The development and implementation of a control assessment process of public procurement in the public sector - MOUKKAR , El Mehdi; HINTI Saïd (Revue du contrôle, de la comptabilité et de l’audit, 2022)
The development and implementation of a process for evaluating internal control of public procurement and financial management plays an important role in ensuring security, transparency and good governance in the public sector. This evaluation process will enable internal control to achieve its main objective which is to ensure the reliability and integrity of the process through which the public order is placed. The effectiveness of this procedure lies in its ability to detect the risks associated with each phase of the public procurement. In this article, we will try through a documentary analysis, to present the role of internal control in the public administration in general and in the risk management of the public order in particular, then we will present the practical process of assessment of internal control according to the COSO standard.